Frequency of Body Weight Loss is an Independent Prognostic Factor of First-Line Treatment Outcomes in Metastatic Colorectal Cancer. (7th February 2022) - Prejac, Juraj; Kekez, Domina; Belev, Borislav; Prejac, Marija; Pleština, Stjepko
Abstract: One of the main features of wasting in cancer is an involuntary weight loss which is most pronounced in gastrointestinal tract tumors and leads to worse clinical outcomes. The aim of this study is to analyze the frequency of body weight loss (FBWL) as an additional prognostic factor in the treatment of patients with metastatic colorectal cancer (mCRC). In this observational, single-center study, data were retrieved for 236 patients treated for mCRC. FBWL was defined as a percent of change in weight divided by weeks of therapy. Patients were stratified into two groups according to the median of FBWL which equaled to the loss of 0.05%/week. Patients who lost >0.05%/week ( N  = 116) had shorter progression-free survival (PFS) in the first-line treatment, then the ones who lost <0.05%/week ( N  = 120); 28.3 vs 46.3 weeks, respectively. Cox regression model showed that FBWL and sidedness were significant predictors of PFS, while age, sex and ECOG were not. Significantly more patients with stable weight were also eligible for second-line treatment. In conclusion, stabilization of body weight is important and independent predictor of longer PFS in first-line therapy of patients with mCRC.